The situation of children in the spaces of selected metropolitan courtyards in the context of Pierre Bourdieu’s concept of reproducing cultural capital - Janik, Agnieszka (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The article addresses the subject of social and cultural inequalities in relation to the situation of children in degraded spaces of selected courtyards in one of the smallest housing estates in Wrocław, Poland, Przedmieście Oławskie. The aim of the research was to diagnose and describe the specific situation of these children and to analyse it in the context of Pierre Bourdieu’s concept of reproducing cultural capital. The first part presents theoretical threads relevant for further interpretations and covers the concepts of marginalisation and reproduction of cultural capital as perceived in P. Bourdieu`s theories. The second part discusses the methodology of qualitative research, embedded in an interpretive paradigm and based on: ethnographicresearch strategy, the approach to research with children and the mosaic approach. The third part presents the results of research showing the specificity of the physical and socio-cultural environment of the studied courtyards. On the one hand, the dimensions of its marginalisation and the processes proving the reproduction of poor cultural capital were indicated; on the other hand, examples of artistic interventions in this type of marginalised environment were presented as exemplifications of breaking the mechanisms of cultural reproduction.